Infections Associated with Intravascular Devices in Adult Patients in a Colombian Hospital - Mora, Javier; Palomino, Leandro; Cabra, Andrea; Álvarez, Camilo (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
Objective: to describe the prevalence of infections associated with devices over a period of 48 months. Material and method: observational cross-sectional study with patients older than 18 years with bacteraemia associated with a device at the San Rafael Clinical University Hospital in Bogotá, Colombia. Results: prevalence of 1.59%, 14.29% were complicated, finding that 60% were endocarditis and 40% were septic thrombosis. Gram-negative bacilli contributed 63.04% mostly Klebsiella pneumonaie. Discussion: prevalence of infections associated with intravascular devices is lower than previously reports.